1978
DOI: 10.1159/000158153
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Calcium in Cyclic Nucleotide Metabolism in Human Vascular Smooth Muscle

Abstract: When cyclic nucleotide phosphodiesterase was purified from isolated smooth muscle layer of human aorta by DEAE-cellulose column chromatography, separated cyclic GMP phosphodiesterase activity was markedly stimulated in the presence of 10–20 µM of Ca2+ by a protein modulator which has similar physico-chemical properties to troponin C. Synthetic compound, N-(6-aminohexyl)-5-chloro-1-naphthalenesulfonamide, which produced relaxations of arteries contracted by prostaglandin F or KCl was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 3 publications
2
30
0
Order By: Relevance
“…In contrast, W-5, which is a less potent calmodulin inhibitor than W-7 (Hidaka et al, 1981), did not show such a protective effect against hypoxia. The concentrations ofW-7 and Cpz in the present experiment are similar to their dissociation constants for calmodulin and certainly lie within the range of their effective concentrations for inhibiting calmodulin-regulated enzyme reactions in vitro (Hidaka et al, 1979;Weiss & Wallace, 1980;Means et al, 1982).…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…In contrast, W-5, which is a less potent calmodulin inhibitor than W-7 (Hidaka et al, 1981), did not show such a protective effect against hypoxia. The concentrations ofW-7 and Cpz in the present experiment are similar to their dissociation constants for calmodulin and certainly lie within the range of their effective concentrations for inhibiting calmodulin-regulated enzyme reactions in vitro (Hidaka et al, 1979;Weiss & Wallace, 1980;Means et al, 1982).…”
Section: Methodssupporting
confidence: 72%
“…Accordingly, an elevation of free Calmodulin, the ubiquitous Ca2+-dependent regulator protein (Cheung, 1980), has attracted a great deal ofattention in recent years, and is now recognized as the major intracellular protein mediating numerous Ca2 -modulated cellular processes, such as cyclic AMP metabolism, glycogen metabolism, cation transport and myosin light chain kinase in the heart (Walsh et al, 1980). The present results showed that hypoxiainduced AH prolongation or AH block was prevented by the pretreatment with W-7 or Cpz, which were reported to be potent calmodulin inhibitors (Levin & Weiss, 1976;Hidaka et al, 1979). In contrast, W-5, which is a less potent calmodulin inhibitor than W-7 (Hidaka et al, 1981), did not show such a protective effect against hypoxia.…”
Section: Methodssupporting
confidence: 52%
“…Although the original discoveries that antipsychotic drugs [Z] and smooth muscle relaxing agents [3,4] bound to CaM led to the suggestion that specific binding sites for these agents may exist, our studies show that identical results are obtained with phenyl-and CAPP-Sepharose, thus indicating that rather non-specific hydrophobic forces must be involved in the interaction between the drugs and the Ca'+-dependent domains on the surface of CaM. Similar conclusions, based on different types of experiments, have been put forward [9,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous func tions of calmodulin are known to be in hibited by W-7. It has been shown that calmodulin-induced activation of cyclic GMP phosphodiesterase of human aorta or bovine brain (2,3), Cat+, Mgt+-ATPase of human erythrocytes (4), myosin light chain kinase of chicken gizzard (5), and phospholipase A2 and C of rat renal medulla (6) are selectively inhibited by W-7. Furthermore, we have reported that W-7 antagonizes the pro longation by calcium of ethanol-induced sleeping time in mice (7,8), and the regula tion by central calcium of blood pressure in rats (9).…”
Section: W-7 (N-(6-aminohexyl)-5-chloro-1-naph Thalenesulfonamide)mentioning
confidence: 99%